2021
DOI: 10.1007/s11013-020-09699-x
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Deprivation, and Dysbiosis: Polyiatrogenesis in Multiple Chronic Illnesses

Abstract: Biomedicine tends to treat “mental” illnesses as if they could be isolated from multiple social and somatic problems. Yet mental suffering is inseparable from complex somatosocial relations. Clinical fieldwork in a deprived area of the UK shows that nearly all the people treated for “depression” are chronically multimorbid, both in their bodies and in their social relations. Mental suffering is co-produced by poverty, trauma, and excessive medication use. Patients’ guts are as imbalanced as their moods. Single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
0
10
0
2
Order By: Relevance
“…My interlocutors’ accounts of reproductive suffering and therapeutic efforts undertaken in tandem with partners, kin, and institutions merged into what I call reproductive chronicity: a form of persistent, yet fluctuating, bodily suffering that is temporarily relieved by ambivalent care options but recurs alongside reproductive events, relations within which care options are located, and structural conditions that shape women's lives. Discussing multimorbidity in a deprived area of the United Kingdom, Ecks (2021: 520) describes “the chronicity of both the problems and of the treatments” and how rather than providing relief, interacting side effects of multiple medications, the lack of follow‐ups or explanations, economic precarity, and social dysfunction can deepen chronic physical and mental conditions. Reproductive chronicity, similarly, captures not only the cumulative effects of catastrophic and ordinary reproductive processes but also available solutions and the efforts required to access them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…My interlocutors’ accounts of reproductive suffering and therapeutic efforts undertaken in tandem with partners, kin, and institutions merged into what I call reproductive chronicity: a form of persistent, yet fluctuating, bodily suffering that is temporarily relieved by ambivalent care options but recurs alongside reproductive events, relations within which care options are located, and structural conditions that shape women's lives. Discussing multimorbidity in a deprived area of the United Kingdom, Ecks (2021: 520) describes “the chronicity of both the problems and of the treatments” and how rather than providing relief, interacting side effects of multiple medications, the lack of follow‐ups or explanations, economic precarity, and social dysfunction can deepen chronic physical and mental conditions. Reproductive chronicity, similarly, captures not only the cumulative effects of catastrophic and ordinary reproductive processes but also available solutions and the efforts required to access them.…”
Section: Discussionmentioning
confidence: 99%
“…The anthropology of chronicity (Ecks 2021; Estroff 1993; Manderson and Smith‐Morris 2010; Manderson and Warren 2016; Weaver and Mendenhall 2014) continues anthropology's interest in documenting suffering (Robbins 2013). Care and chronicity are closely linked, but this link often remains implicit.…”
Section: Care and Chronicitymentioning
confidence: 99%
“…Therefore, it is essential for our society (and patients) that vulnerable patients with multimorbidity and polypharmacy be empowered to better care for themselves. However, at the same time, Ecks’ recent study has shown that socioeconomic hardship and inequality make it more difficult for people from disadvantaged backgrounds to engage actively in treatment decision-making [ 43 ]. The importance of social inequality in multimorbidity is emphasized further in Barrett et al‘s study on multimorbidity, which reveals that the onset of multimorbidity occurs ten to fifteen years earlier in socially deprived areas, calling into question the existing single disease treatment approach in healthcare [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, people with multiple chronic conditions are especially vulnerable to the detrimental effects of too much medicine. In a recent study of a health centre in "one of the most deprived areas" of the UK, Ecks (2021) found that patients are often harmed by what he calls 'polyiatrogenesis', the unintended but nevertheless harmful effects of many uncoordinated interventions. Through case studies of people with physical and mental multimorbidities, he argues that treatments targeted specifically on one disease often culminate in complex effects, and risk overtreatment and polypharmacy.…”
Section: Multimorbidity and The Limits Of Contemporary Care Servicesmentioning
confidence: 99%